Biomedical and pharmacological potential of tetrodotoxin-producing bacteria isolated from marine pufferfish Arothron hispidus (Muller, 1841) - Bragadeeswaran,S (2010)
Specimens of the pufferfish Arothron hispidus collected at Parangipettai, on the southeast coast of India, were subjected to bacterial isolation and identification. Three species were identified, namely Bacillus sp., Kytococcus sedentarius and Cellulomonas fimi. Partially-purified microbial filtrates exhibited hemolytic activity on chicken and human erythrocytes of O, B and AB blood groups, with maximum activity of 32 HU. The microbial filtrates also presented ATPase, Mg2+-ATPase, Na+K+-ATPase and AchE enzymatic activities of positive neuromodulation in Kytococcus sedentarius with 1300, 300.1, 1549.98 and 140.55%, in Cellulomonas fimi with 620, 300, 10 and 128.42%, and in Bacillus species with 40, 200, 849.98 and 158.69%, respectively. Toxicity symptoms were observed when the bacterial filtrate was intraperitoneally injected into mice. The bacterial filtrate caused adverse effects on viability of the mouse muscle cell line (L929) and leukemia cell line (P388). Maximum level of inhibition was observed on the growth of L929 cell line. Bacillus lentimorbus inhibited the cell line from 84.03 to 94.43% whereas Bacillus species inhibited the growth in a range between 77.25 and 86.16% at the lowest dilution.